Chance, Imitative, and Strategic Antecedents to Multimarket Contact - Korn, Helaine J.; Baum, Joel A. C. (Academy of Management Journal, 1999)
We redirect research attention on multimarket contact from its consequences to its antecedents. Our empirical examination of the evolution of dyadic multimarket contacts among California commuter airlines from 1979 through 1984 reveals that multimarket contact arises from chance market contacts among competitors pursuing uncoordinated strategies, trait-based imitation unrelated to multimarket contact, vicarious learning related to multimarket contact, and strategic attempts to develop multimarket contact based on insight gained through experiential learning.